The Impact of Continuous Veno-Venous Hemodiafiltration on the Efficacy of Administration of Prophylactic Doses of Enoxaparin: A Prospective Observational Study - Aleksander Aszkiełowicz; Karol P. Steckiewicz; Michał Okrągły; Magdalena A. Wujtewicz; Radosław Owczuk (MDPI AG, 2023)
Background: Critically ill patients frequently require continuous renal replacement therapy (CRRT). During CRRT, particles up to 10 kDa in size, such as enoxaparin, may be removed. The aim of this study was to determine if patients receiving prophylactic doses of enoxaparin and treated with continuous veno-venous hemodiafiltration (CVVHDF) reach prophylactic values of anti-Xa factor activity. Methods: In this observational trial, we compared two groups: 20 patients treated with CVVHDF and 20 patients not treated with CVVHDF. All of them received prophylactic doses of 40 mg of enoxaparin subcutaneously. Anti-Xa factor activity was determined on the third day of receiving a prophylactic dose of enoxaparin. The first blood sample was taken just before the administration of enoxaparin, and other samples were taken 3 h, 6 h, and 9 h after the administration of a prophylactic dose of enoxaparin. Results: At 3 and 6 h after administration of enoxaparin in both groups, we observed a significant increase in anti-Xa factor activity from baseline, with the peak after 3 h of administration. There were no significant differences in the numbers of patients who had anti-Xa factor activity within the prophylactic range between CVVHDF and control groups. Conclusion: CVVHDF has only a mild effect on the enoxaparin prophylactic effect measured by anti-Xa factor activity. Thus, it seems there is no need to increase the dose of enoxaparin for patients requiring CVVHDF.